# Thread: solvind simple equations

1. ## solvind simple equations

-r + 18 = -39 ... -r +18-18 = -39 + -18 = -r + 0 = -57. my study gude says the answer is 57 can someone please help me understand how the answer could be 57. and not -57

2. Originally Posted by Leona_Marie
-r + 18 = -39 ... -r +18-18 = -39 + -18 = -r + 0 = -57. my study gude says the answer is 57 can someone please help me understand how the answer could be 57. and not -57

-r=-57 , note that there are negative signs at both sides , cancelling both the signs , you should get r=57 .

3. Originally Posted by mathaddict
-r=-57 , note that there are negative signs at both sides , cancelling both the signs , you should get r=57 .
but 57 + 18 doesnt = -39 please explain

4. Originally Posted by Leona_Marie
but 57 + 18 doesnt = -39 please explain

Alright , lets start from the begining again.

-r + 18 = -39
-r +18 -18 =-39-18

-r=-57

r=57

How did u come to this , 57 + 18 doesnt = -39 ??

5. .(how do i delete this mmessage didnt mean to post it?

6. Originally Posted by mathaddict
Alright , lets start from the begining again.

-r + 18 = -39
-r +18 -18 =-39-18

-r=-57

r=57

How did u come to this , 57 + 18 doesnt = -39 ??
yes I am new to this I figure -r + 18 should equal -39
if the answer is 57, well 57+18 is 75 but-57 +18 = -39 Im confused

7. Originally Posted by Leona_Marie
yes I am new to this I figure -r + 18 should equal -39
if the answer is 57, well 57+18 is 75 but-57 +18 = -39 Im confused
Hi Leona,

It's very simple. Watch

$\displaystyle -r+18=-39$

First we subtract 18 from both sides giving us:

$\displaystyle -r+18-18=-39-18$

$\displaystyle -r=-57$

But, we're not done. We must find a solution for r, not -r. To find r, we multiply both sides of the equation by -1.

$\displaystyle (-1)(-r)=(-1)(-57)$

$\displaystyle \boxed{r=57}$

To check this we start with our original equation:

$\displaystyle -r+18=-39$

Substitute 57 in for r to get:

$\displaystyle -(57)+18=-39$

Notice, the negative sign was already part of the equation. I just replaced r with 57. Now the check is fine.

$\displaystyle -57+18=39$
$\displaystyle -39=-39$

8. this is the second time you helped me to understand Id like to thank you but still I dont know where the thank but is exactly.